Robotic-assisted thyroidectomy: a new experience in anaesthesia - Mardhiah Sarah Harnani Mansor; Adlin Dasima AK; Nadia Hanom I; Siti Aznida AK; Rusnaini MK; Mohd Fahmi Z; Mohd Nazir MS; Izwah Azyyati A; Mohd Firdaus S; Karis M (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
This is our first experience in providing general anaesthesia for robotic-assisted thyroidectomy (RAT). It is rather a new experience for our anaesthetic team and few issues should be addressed. The conduct of RAT must be fully understood and familiarized as it may present with few challenges for the anaesthesiologists. The key point of success during this learning curve period is the importance of teamwork between the anaesthesiologists and the operating surgeons. The specific anaesthetic challenges include limited access to the patient post-docking of the robot, the need of extra precautions of the anaesthetic circuit and IV line connections, a vigilant anaesthesiologists and options for postoperative pain relief.